Are Hispanic immigrant families reviving the economies of America's small towns? - Dennis Coates; T. H. Gindling (Institute for the Study of Labor (IZA), 2010)
In the 1990s, rural areas and small towns in the United States, which had been losing population, became the destinations for an increasing number of Hispanic immigrants and their families, slowing and in some cases reversing population declines. In this paper, we examine whether faster growth in the Hispanic population is linked to faster growth in income per capita in rural areas and small towns. Our results indicate strong support for the hypothesis that Hispanic population growth has fueled increased economic growth in those small, rural communities whose populations had been in decline during the 1970s and 1980s.
Keywords: R11; R23; O4; 330; Regional economic growth; Hispanics; migration; Migranten; Hispano-Amerikaner; Ländliche Entwicklung; Dorfentwicklung; USA